2013
DOI: 10.1200/jco.2013.31.18_suppl.3
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of bevacizumab in the treatment of recurrent and metastatic cervical cancer: A phase III randomized trial of the Gynecologic Oncology Group.

Abstract: 3 Background: Vascular endothelial growth factor (VEGF) promotes angiogenesis, a mediator of disease progression in cervical cancer. Bevacizumab (B), a humanized anti-VEGF monoclonal antibody, has shown single-agent activity in pretreated recurrent disease. We aimed to evaluate B in chemotherapy (CTX)-naive recurrent/persistent/metastatic cervical cancer. Methods: Using a 2x2 factorial design, patients were randomly assigned to CTX with or without B 15 mg/kg. The CTX regimens included cisplatin 50 mg/m2 plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Recently, a 4-arm, phase III trial including a platinumbased combination regimen with or without the molecularly targeted agent bevacizumab and a nonYplatinum-based combination regimen with or without bevacizumab was performed in patients with advanced or recurrent cervical cancer. 16 The results showed that concurrent and sustained administration of bevacizumab substantially prolonged OS. Bevacizumab is also known to prolong PFS in ovarian cancer, not only when used with multiple agents in platinum-sensitive cases, 17 but also in conjunction with a single agent in platinum-resistant cases.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a 4-arm, phase III trial including a platinumbased combination regimen with or without the molecularly targeted agent bevacizumab and a nonYplatinum-based combination regimen with or without bevacizumab was performed in patients with advanced or recurrent cervical cancer. 16 The results showed that concurrent and sustained administration of bevacizumab substantially prolonged OS. Bevacizumab is also known to prolong PFS in ovarian cancer, not only when used with multiple agents in platinum-sensitive cases, 17 but also in conjunction with a single agent in platinum-resistant cases.…”
Section: Discussionmentioning
confidence: 98%
“…30 Furthermore, standard of care combinations of platinum based chemotherapy and radiotherapy for the primary, potentially “curative” treatment of stage IB-IV cervical cancer have remained largely unchanged since the 1990s, as has outcome. 31–34 In some respects, our understanding of the biological and molecular heterogeneity of this disease has lagged behind that of other cancers.…”
Section: Cervical Pdx Models26mentioning
confidence: 99%
“…In the plenary session of the 2013 American Society of Clinical Oncology (ASCO) Annual Meeting in Chicago, Dr. Tewari presented the interim analytical results of a phase III randomized trial conducted by the Gynecologic Oncology Group (GOG), GOG 240, which regarded the incorporation of BEV for the treatment of recurrent and metastatic cervical cancers [1]. A total of 452 patients with metastatic, recurrent, or persistent cervical cancers that were incurable with standard treatments were enrolled in this study and randomized to one of four treatment arms: (1) cisplatin (50 mg/m 2 ) plus paclitaxel (135 to 175 mg/m 2 ) alone; or (2) with BEV; or (3) topotecan (0.75 mg/m 2 on days 1 to 3) plus paclitaxel (175 mg/m 2 on day 1) alone; or (4) with BEV.…”
Section: Bevacizumab: a New Hope For Recurrent/metastatic Cervical Camentioning
confidence: 99%